Formulasi Paham Mistik-Keagamaan dalam Tradisi Kepimpinan Jawa dan Kontribusinya bagi Kepimpinan Nasional - Farid Farid; Mustofa Anshori Lidinillah (Jurnal Filsafat "WISDOM", 1999)
The methodical aspects to analyze these research are interpretation, intern-coherency, holistical, and heuristical methods.The power in Javanese tradition is a metaempirical ideas that metaphysically is The successfully leadership will bring a good social order and the fail leadership will cause a chaos society. To reach the succesfully religion is used to legitimate the leadership sometime, everthought this way brings a negative aspect.This research will explain how mystic-religion ideas or religions influence a Javanese leadership, and its contribution to national leadership. This research is a libralian research. The material object of this research is to the tradition of Javanese leadership reached to the spiritual activity to accumulate the cosmic power in to a leader itself.The leadership therefore, is valid because sources from adikodrati power. The manunggaling kawula Gusti as religion-mystic ideas does not only explain relation between a leader with God, but between a leader with people also.The power of Javanese ideas usefull for national leadership development. It is important to remain that in the leadership personality there is a cosmic harmony. Believing to God and concern to the people are requierment in building a tight leadership.